Effect of a new health education model on continuous nursing in elderly patients with diabetes mellitus - Chao Jing-Jing; Xue Ya-Zhuo (Sciendo, 2018)
We aimed to explore the effect of a new health education model on continuous nursing care in elderly patients with diabetes mellitus who had undergone an operation for fracture.